Platelet-Released Growth Factors and Platelet-Rich Fibrin Induce Expression of Factors Involved in Extracellular Matrix Organization in Human Keratinocytes - Bayer, Andreas (Int J Mol Sci, 2020)
Platelet-released growth factor (PRGF) is a thrombocyte concentrate lysate which, like its clinically equivalent variations (e.g., Vivostat PRF(®) (platelet-rich fibrin)), is known to support the healing of chronic and hard-to-heal wounds. However, studies on the effect of PRGF on keratinocytes remain scarce. This study aims to identify genes in keratinocytes that are significantly influenced by PRGF. Therefore, we performed a whole transcriptome and gene ontology (GO) enrichment analysis of PRGF-stimulated human primary keratinocytes. This revealed an increased expression of genes involved in extracellular matrix (ECM) organization. Real-time polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) analysis confirmed the PRGF-mediated induction of selected ECM-related factors such as transforming growth factor beta-induced protein, fibronectin 1, matrix metalloproteinase-9, transglutaminase 2, fermitin family member 1, collagen type I alpha 1 and collagen type XXII alpha 1. PRGF-induced expression of the above factors was influenced by blockade of the epidermal growth factor receptor (EGFR), a receptor playing a crucial role in wound healing. A differential induction of the investigated factors was also detected in skin explants exposed to PRGF and in experimentally generated in vivo wounds treated with Vivostat PRF(®). Together, our study indicates that the induction of ECM-related factors may contribute to the beneficial wound-healing effects of PRGF-based formulations.